The Impact Of Tourism Development On The Ecosystem In Residential Areas According To Law 32 Of 2009 - Khayla Khairunnisa; Deni Yusup Permana (Ann Publisher, 2026)
Background. The development of illegal tourism infrastructure in residential areas has triggered ecosystem degradation, with a direct impact on the quality of the environment and the welfare of local communities, thereby contravening the principles of environmental protection stipulated in Law Number 32 of 2009 concerning Environmental Protection and Management. Weak supervision and implementation of environmental permits exacerbate the risk of ecological damage in residential areas. Aims. This research aims to analyze the compensation mechanism for residents affected by ecosystem damage and examine the effectiveness of environmental mitigation efforts within the applicable legal framework. Method. This research employs a normative juridical method, with a legislative approach, through an analysis of legal norms, environmental law principles, and relevant legal documents. Results. The results of the study show that the affected community has the right to file a civil lawsuit or class action based on the principle of strict liability to obtain material, immaterial, and environmental restoration damages. Mitigation efforts are carried out through the stages of prevention (EIA), pollution control, and restoration of ecosystem function.Conclusion. This study concludes that although the legal framework has comprehensively regulated protection and mitigation mechanisms, its effectiveness is still hampered by weak field supervision, so it is necessary to strengthen the licensing and environmental supervision system to realize sustainable and equitable tourism development.